KEMAMPUAN BERPIKIR KREATIF SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA ULAR TANGGA PADA MATERI ENERGI DALAM SISTEM KEHIDUPAN - Latjompoh, Masra; Odja, Abdul Haris; Toonawu, Novita (Universitas Tadulako, 2021)
This study aims to determine the effect of cooperative learning model type TGT assisted by snake and ladder media on energy material in living systems to increase students' creative thinking skills. The method used in this study is a quasi-experimental, with the research subjects being class VII students of SMP Negeri 1 Limboto. The research design used a one-group pretest-posttest design. Research data on students' initial creative thinking abilities are seen from the characteristics of creative thinking in the form of fluency of 48.3, flexibility of 13.1, and originality of 14.8. After the treatment was given a posttest with the results of each characteristic of the ability to think creatively in the fluency category with a total of 68.8, the flexibility category of 70.7 and the originality category of 33.9. The average N-gain of students' creative thinking abilities in the fluency category is 0.36, flexibility is 0.66, and originality is 0.22. Based on N-Gain, there was an increase in the creative thinking ability of grade VII 4 students of SMP Negeri 1 Limboto, but the increase was in the medium category. Students still have the initial level of creative thinking skills.